Visible Light Active Silver Decorated Iron Titanate/Titanium Dioxide Nanohybrid for Sterilization of Explants Grown by In Vitro Technique. Issue 6 (4th December 2022) - Seneviratne, Kasun L.; Munaweera, Imalka; Peiris, Sriyani E.; Kodithuwakku, Piyumi; Peiris, Colin N.; Kottegoda, Nilwala
Abstract: Visible light (VL) active silver decorated iron titanate/titanium dioxide (Ag‐FeTiO3 /TiO2 ) nanohybrids derived from natural ilmenite sand effectively cleanse the exophytic plant pathogens in explants grown by in vitro techniques. VL active nanohybrid is synthesized by acid‐hydrolysis of natural ilmenite, followed by precipitation of the lixivium and decoration with Ag onto FeTiO3 /TiO2 nanoparticles, and finally calcination under a nitrogen environment to obtain Ag‐FeTiO3 /TiO2 . A morphological study conducted using transmission electron microscopy (TEM) confirms the formation of Ag‐FeTiO3 /TiO2 . Powder X‐ray diffraction (PXRD) analysis shows that the nanohybrid primarily consists of anatase, iron titanate (FeTiO3 ), Ag2 O, and Ag. X‐ray photoelectron spectroscopy (XPS) study suggests the presence of Ag 0 /Ag2 O/Fe2 O3 composites on the FeTiO3 /TiO2 particle surface. The optical band gap significantly changes from 3.14 eV (ilmenite) to 2.80 eV after the decoration of FeTiO3 /TiO2 with Ag. This nanohybrid is utilized as a surface‐sterilizing agent for in vitro establishment of the Dracaena sanderiana Sander ex Mast plant. Findings illustrate Ag‐FeTiO3 /TiO2 nanohybrid‐based photo‐sterilization leads to the survival of 90% of the microbes' free cultures while the material can be re‐used due to its photocatalytic behavior. Thus, the newly synthesized nanohybrid can replace harmful sterilization agents used in tissue culture techniques. Abstract : Natural ilmenite‐derived visible light active Ag‐FeTiO3 /TiO2 nanohybrid is a more successful and eco‐friendly sterilization material by restricting toxic disinfecting chemicals.